Numerical analysis of cracked railway bridge decks subjected to cyclic loading - Carlos Sousa (2012)
In this paper, a recently developed numerical model for analysis of the cyclic behaviour ofcracked reinforced concrete beams is applied to the study of the mechanical response of cracked railwaybridge decks. This numerical methodology includes constitutive models to describe the local bond stress-sliprelationship, taking into account the effects of cyclic loading. The local relationship between the normal stressto the crack and the crack opening under cyclic loading is also explicitly considered in the numerical model.Relevant analysis results are presented and discussed.